215k views
3 votes
(x² + 6x + 1) = (x – 3)

2 Answers

3 votes


\sf{\underline{\boxed{\green{\large{\bold{ Solution}}}}}}


\sf\implies x^2 + 6x + 1 = x - 3


\sf\implies x^2 + 6x - x + 1 + 3 = 0

⠀⠀⠀⠀


\sf\implies x^2 + 5x + 4 = 0

⠀⠀⠀⠀⠀⠀⠀

compare the eq with
\sf{\underline{\bold{ax^2 + bx + c = 0 }}}

⠀⠀⠀⠀⠀⠀⠀

☯ a = 1

☯ b = 5

☯ c = 4

⠀⠀⠀⠀⠀⠀⠀

now :-

⠀⠀⠀⠀⠀⠀⠀


\sf{\underline{\boxed{\pink{\large{\mathfrak{x = ( - b \pm \sqrt D )/(2a )}}}}}}

⠀⠀⠀⠀⠀⠀⠀


\sf{\underline{\boxed{\pink{\large{\mathfrak{ D = b^2 - 4ac }}}}}}

⠀⠀⠀⠀⠀⠀⠀

finding value of D.

⠀⠀⠀⠀⠀⠀⠀


\sf\implies D = b^2 - 4ac


\sf\implies D = (5)^2 - 4 * 1 * 4


\sf\implies D = 25 - 16

⠀⠀⠀⠀


\sf\implies D = 9


\sf{\underline{\boxed{\blue{\large{\bold{ D = 9}}}}}}

⠀⠀⠀⠀⠀⠀⠀

putting values in the eq.

⠀⠀⠀⠀⠀⠀⠀


\sf\implies x = ( -b \pm\sqrt D )/(2a)


\sf\implies x = \frac{ -( 5) \pm\sqrt {9} }{2* 1 }


\sf\implies x = ( -5 \pm 3 )/(2)

⠀⠀⠀⠀⠀⠀⠀


\sf x = ( -5 + 3 )/( 2 )


\implies x = \frac {-2}{2}


\implies x = -1


\sf{\underline{\boxed{\purple{\large{\bold{ x = -1 }}}}}}

⠀⠀⠀⠀⠀⠀⠀

⠀⠀⠀⠀⠀⠀⠀

⠀⠀⠀⠀⠀⠀⠀


\sf x = ( -5 - 3 )/( 2 )


\implies x = \frac {-8}{2}


\implies x = -4


\sf{\underline{\boxed{\purple{\large{\bold{ x = -4 }}}}}}

⠀⠀⠀⠀⠀⠀⠀


\sf{\underline{\boxed{\purple{\large{\bold{ x = -1 \: or \:-4 }}}}}}

User Domkck
by
4.6k points
2 votes

Hello!


\large\boxed{x = -4, -1}

x² + 6x + 1 = x - 3

Bring all terms to one side by subtracting x and adding 3:

x² + 6x - x + 1 + 3 = x - x - 3 + 3

x² + 5x + 4 = 0

Factor:

(x + 4)(x + 1) = 0

Set each factor to 0:

x + 4 = 0

x = -4

x + 1 = 0

x = -1

User Pila
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.